2015
DOI: 10.1097/jom.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Use by Documented and Undocumented Farm Workers

Abstract: Undocumented farm workers' households were roughly half as likely to use Medicaid as documented households, and undocumented households' participation was especially responsive to the presence of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It should be noted, however, that Medicaid use is significantly less among undocumented immigrants than among documented immigrants [19]. Namely, While undocumented and non-citizen immigrant groups are very similar in most demographic characteristics, they vary significantly on their type of coverage.…”
Section: Discussionmentioning
confidence: 89%
“…It should be noted, however, that Medicaid use is significantly less among undocumented immigrants than among documented immigrants [19]. Namely, While undocumented and non-citizen immigrant groups are very similar in most demographic characteristics, they vary significantly on their type of coverage.…”
Section: Discussionmentioning
confidence: 89%
“…The 12.2% SNAP and 18.0% WIC participation rates measured in this study are on the low end of recent estimates for U.S. farmworkers, ranging from 15–32% for SNAP and 13–22% for WIC [ 29 ]. Several studies using the NAWS have found that legal status has little direct association with SNAP and WIC participation rates among farmworkers [ 30 32 ]. Still, it may be challenging to capture unbiased SNAP/WIC participation.…”
Section: Discussionmentioning
confidence: 99%